BEHAVIORAL FACTORS INFLUENCING THE USE OF RURAL DEVELOPMENT SUPPORT - Kotevska, Ana; Martinovska Stojcheska, Aleksandra; Dimitrievski, Dragi (Faculty of Agricultural Sciences and Food - Skopje, 2016)
Rural development (RD) policy is essential for sustainable development and continuous improvement of the quality of life of rural people. Despite the relative importance of RD policy, its implementation is lagging behind the direct payments support, partly because of the farmers’ unengaged interest. The aim of this paper is to identify the key behavioral factors that influence farmers’ intention to apply for RD support. The analytical framework is based on the theory of planned behavior, where the individual intention to perform a given behavior (apply for RD support) determines the performance and is shaped by the individual attitudes, social support and the perceived behavioral control; and a structural equation model. The survey took place in November-December 2014, in face-to-face interviews covering 299 farm households in Macedonia. Farmers with more positive attitude and perceived behavioral controls have stronger intention to use the RD support available. The model explains two-thirds of the variance. This knowledge provides basis for designing interventions to maximize farmers’ use of available rural development funds.
Keywords: Rural development support, Macedonia, Theory of planned behavior, Structural Equation Model